Business cycle for the Covid-19 recession - Fernandes, Daniel Gomes (2022)
We apply the Business Cycle Accounting framework to the COVID-19 recession in the Euro Area and the United States. We conclude that the efficiency wedge had the most important role in the Euro Area, followed by the labor and investment wedges. In the United States, the labor wedge was most crucial, with the investment wedge taking a second place. We present hypotheses, supported by our theoretical framework, for the dichotomy of the role of the efficiency wedge between the studied regions.Keywords:Economics,COVID-19, Business Cycle Accounting, Macroeconomics, Financial Crises, Financial Frictions, Wedges